Implementasi Lean Manufacturing untuk Optimasi Rendemen dan Peningkatan Efisiensi Biaya pada Produksi Farmasi Sediaan Semisolid: Studi Kasus pada Krim Miconazole - Prisma Wahyuning Inayah; Agnes Nuniek Winantari; Endang Wahyu Fitriani (Jurnal Penelitian Pendidikan IPA, 2026)
Yield loss due to overfill during the filling process remains a major source of material waste and increased production costs in semisolid pharmaceutical manufacturing. This study aimed to implement a lean manufacturing approach to optimize production yield and improve cost efficiency in miconazole cream production. A quantitative descriptive case study was conducted on the semisolid production line of an Indonesian pharmaceutical company. Data were collected through direct observation, production records, in-process control (IPC) records, and historical operational data. Value Stream Mapping (VSM) and fishbone diagram analysis were used to identify waste and determine the root causes of process inefficiencies, while a before–after analysis evaluated the effectiveness of the implemented improvements. The filling process was identified as the primary source of process variability and overfill. Improvement actions, including holder position adjustment, tightening of fill weight specifications, and increased IPC frequency, reduced the average fill weight from 10.315 g to 10.115 g and increased production yield from 97.18% to 98.20%. These improvements generated an average cost saving of IDR 113,924 per batch, equivalent to a potential annual cost efficiency of IDR 134,771,855. The findings demonstrate that lean manufacturing effectively reduces process variability, improves production yield, and enhances cost efficiency in semisolid pharmaceutical manufacturing.